Incidence and Risk Factors of Zidovudine-Induced Anemia in Patients With HIV Infection Receiving Zidovudine-Containing Antiretroviral Therapy - Lakkana Boonyagars MD, MSc; Peerawit Thinpangnga MSc; Warangkana Munsakul MD (Journal of the International Association of Providers of AIDS Care)
Background Anemia is among the frequently observed conditions among people living with HIV (PLWH). Zidovudine (AZT) is the most common ART that causes anemia. This study aimed to identify the incidence and risk factors of AZT-induced anemia in PLWH receiving AZT-containing regimens. Methods A retrospective cohort study was conducted on nonpregnant PLWH aged >18 years who received AZT-containing regimens for >6 months and had normal baseline hemoglobin levels. Data on medical history, clinical characteristics, and laboratory examination were collected. Cox proportional hazard regression analysis was performed to determine the risk factors of AZT-induced anemia. Results A total of 401 individuals were included in the study. In total, 71 individuals presented with AZT-induced anemia. The incidence rate of anemia was 1.98 per 100 person-years of observations. Female sex, low-normal baseline hemoglobin level, low recent and low baseline CD4 cell count were independently associated with an increased risk of anemia. However, a higher body mass index was independently associated with a decreased risk of anemia. Conclusion Routine screening, early detection, and treatment of anemia should be considered in PLWH receiving AZT-containing regimens.